Analisis Pengukuran Indeks Literasi Zakat Pada Masyarakat Kota Tangerang Selatan - Salmarani Salsabila; Muhammad Nadratuzzaman Hosen (JES (Jurnal Ekonomi Syariah), 2022)
This study aims at measuring Zakat Literacy Index (ILZ) of the people of South Tangerang City using the Simple Weighted Index method, which focuses on measuring a person's level of understanding and literacy on the object of zakat. Literacy and understanding of zakat become the external factors that can determine people to pay zakat. The results reveal that Zakat Literacy Index in South Tangerang City obtains a value of 81.78 which was included in the high literacy category. The highest indicator is the knowledge variable about the obligation to pay zakat with a score of 95.25. And the lowest indicator in this measurement lies in the knowledge variable about zakat regulation with a score of 48.67.